Mortality Benefit of Convalescent Plasma in COVID-19: A Systematic Review and Meta-Analysis - Bansal, Vikas; Mahapure, Kiran S.; Mehra, Ishita; Bhurwal, Abhishek; Tekin, Aysun; Singh, Romil; Gupta, Ishita; Rathore, Sawai Singh; Khan, Hira; Deshpande, Sohiel; Gulati, Shivam; Armaly, Paige; et al. (Frontiers in Medicine, 2021)
Importance/Background: With a scarcity of high-grade evidence for COVID-19 treatment, researchers and health care providers across the world have resorted to classical and historical interventions. Immunotherapy with convalescent plasma (CPT) is one such therapeutic option. Methods: A systematized search was conducted for articles published between December 2019 and 18th January 2021 focusing on convalescent plasma efficacy and safety in COVID-19. The primary outcomes were defined as mortality benefit in patients treated with convalescent plasma compared to standard therapy/placebo. The secondary outcome was pooled mortality rate and the adverse event rate in convalescent plasma-treated patients. Results: A total of 27,706 patients were included in the qualitative analysis, and a total of 3,262 (2,127 in convalescent plasma-treated patients and 1,135 in the non-convalescent plasma/control group) patients died. The quantitative synthesis in 23 studies showed that the odds of mortality in patients who received plasma therapy were significantly lower than those in patients who did not receive plasma therapy [odds ratio (OR) 0.65, 95% confidence interval (CI) 0.53–0.80, p < 0.0001, I2 = 15%). The mortality benefit remains the same even for 14 trials/prospective studies (OR 0.59, 95% CI 0.43–0.81, p = 0.001, I2 = 22%) as well as for nine case series/retrospective observational studies (OR 0.78, 95% CI 0.65–0.94, p = 0.01, I2 = 0%). However, in a subgroup analysis for 10 randomized controlled trials (RCTs), there was no statistically significant reduction in mortality between the CPT group compared to the non-CPT group (OR 0.76, 95% CI 0.53–1.08, p = 0.13, I2 = 7%). Furthermore, the sensitivity analysis of 10 RCTs, excluding the study with the highest statistical weight, displayed a lower mortality rate compared to that of non-CPT COVID-19 patients (OR 0.64, 95% CI 0.42–0.97, p = 0.04, I2 = 0%). The observed pooled mortality rate was 12.9% (95% CI 9.7–16.9%), and the pooled adverse event rate was 6.1% (95% CI 3.2–11.6), with significant heterogeneity. Conclusions and Relevance: Our systemic review and meta-analysis suggests that CPT could be an effective therapeutic option with promising evidence on the safety and reduced mortality in concomitant treatment for COVID-19 along with antiviral/antimicrobial drugs, steroids, and other supportive care. Future exploratory studies could benefit from more standardized reporting, especially in terms of the timing of interventions and clinically relevant outcomes, like days until discharge from the hospital and improvement of clinical symptoms.